2014
DOI: 10.1371/journal.pone.0089825
|View full text |Cite
|
Sign up to set email alerts
|

Model-Observer Similarity, Error Modeling and Social Learning in Rhesus Macaques

Abstract: Monkeys readily learn to discriminate between rewarded and unrewarded items or actions by observing their conspecifics. However, they do not systematically learn from humans. Understanding what makes human-to-monkey transmission of knowledge work or fail could help identify mediators and moderators of social learning that operate regardless of language or culture, and transcend inter-species differences. Do monkeys fail to learn when human models show a behavior too dissimilar from the animals’ own, or when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…Previous studies reported similar learning abilities in the interaction with humans 9,20,26 . Monfardini et al .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies reported similar learning abilities in the interaction with humans 9,20,26 . Monfardini et al .…”
Section: Discussionsupporting
confidence: 53%
“…The object-in-place paradigm 30,31 has been used recently in primates to study rapid learning about the relative value of unfamiliar stimuli 32 . Alongside this, several studies demonstrated that rhesus macaques can monitor the action of another partner 5,21 and learn from the observation of a conspecific 6,33 or a human 9,20 . To compare social and non-social observational learning (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to testing other great apes, it would be useful to expose participants to incorrect as well as correct responses. Errors, executed by conspecifics, have been associated with more robust social learning in both children (19,20,46) and monkeys (47,48). This would reveal whether the pattern of results reported here would change if apes and children were provided with models that showed both correct and incorrect responses.…”
Section: Discussionmentioning
confidence: 59%
“…Based on the social cognitive theory, role modelling can be used as a method to increase self-efficacy (Bandura, 1977). The success of modelling is highly influenced by the identifiability of the role model (Meltzoff, 2007;Monfardini, Hadj-Bouziane, & Meunier, 2014). Some home-care workers mentioned that the interventionist had sometimes unrealistic expectations regarding the application of reablement in practice.…”
Section: Experiences With Regard To Improvements In Self-efficacymentioning
confidence: 99%